Co-cultivation of microalgae growing on palm oil mill effluent under outdoor condition for lipid production. Issue 1 (31st December 2022) - Nur, Muhamad Maulana Azimatun; Djarot, Ira Nurhayati; Boelen, Peter; Hadiyanto,; Heeres, Hero Jan
ABSTRACT: POME is an excellent cultivation medium for the production of microalgae because it includes high macro and micronutrients. Nevertheless, microalga cultivation is laborious to maintain under outdoor condition. The aim of this reseasch was to evaluate the potency of co-cultivation strategy to improve growth and lipid production of mixed algae when growing on POME under dynamic outdoor condition. Cultivation was done in outdoor condition by comparing synthetic medium and POME medium, and optimizing the enviromental and nutritional conditions by using Box-behnken response surface methodology (RSM). Results showed that high growth rate (0.35/d) and lipid (40%) were achieved when 75% POME fraction, 30 PSU salinity, and 450 mg/L urea were used. The increasing POME fraction and urea addition enhanced SFA formation to MUFA and PUFA in the fatty acid profiles. We conclude that co-cultivation strategy on POME could promote growth rate and lipid production of mixed algae under outdoor condition.